Things we haven't said : sexual violence survivors speak out - Moulton, Erin E.; Andrews, Ella.; Black, Dina.; Capri, Imani; Carmer-Hall, Jennifer; Clare, Joan.; Cochrane, Jane.; Cribbs, G. Donald; Demri, Maya.; Edwardson, Aaluk; Hanen, Sharon Abra. (San Francisco, CA : Zest Books, 2018)
Shares twenty stories from diverse survivors of childhood sexual violence, explaining how they overcame the boundaries of stigma and silence to help prevent trauma and loss of life.
On title page, title has a line through it.
Includes bibliographical references (pages 204-207).
Keywords: Adult child sexual abuse victims -- Anecdotes -- Juvenile literature; Sexual abuse victims -- Anecdotes -- Juvenile literature; Rape victims -- Anecdotes -- Juvenile literature; Incest victims -- Anecdotes -- Juvenile literature; Sexual abuse -- Anecdotes; Rape victims -- Anecdotes; Incest victims -- Anecdotes; Child sexual abuse -- Anecdotes; Sex crimes -- Anecdotes; Rape -- Anecdotes; Incest -- Anecdotes